Global Citizen and Shared Responsibility: Addressing the Rohingya Refugee Crisis in Indonesia - Paripurna, Clarissa Fortuna; Ragilia Dwi Pradita; Silvana Putri Priageng; Aniqotul Ummah (PT ARRUS Intelektual Indonesia, 2024)
The Rohingya refugee crisis is one of the humanitarian issues that has received a lot of public attention. The issue of ethnic violence against the Rohingya has emerged since Myanmar did not recognize them as citizens. This wave of refugees arrived in Indonesia in 2009 and continued in 2023, precisely in Aceh. The purpose of this study is to analyze the role of global citizenship in responding to and handling the Rohingya refugee crisis in Indonesia. Not only that, the purpose of this study also aims to describe the challenges faced and the impacts caused by the presence of Rohingya refugees in Indonesia. The method used in this study uses qualitative case study-based methods. This study uses data obtained from reading journals, articles and books that are in accordance with the discussion topics chosen by the researcher. The case study approach is used to make it easier for the author to elaborate and explain what global citizenship is and its role in world-level problems, one of which is the problem of Rohingya refugees. This study proves that global citizenship cannot provide much change for Rohingya refugees. In Indonesia itself, there is no policy that can really help Rohingya refugees, as well as at the world level. With the implementation of a more integrated global citizenship, solutions regarding Human Rights can be realized.